2016
DOI: 10.1097/aln.0000000000000994
|View full text |Cite
|
Sign up to set email alerts
|

Mild Sedation Exacerbates or Unmasks Focal Neurologic Dysfunction in Neurosurgical Patients with Supratentorial Brain Mass Lesions in a Drug-specific Manner

Abstract: Background Sedation is commonly used in neurosurgical patients but has been reported to produce transient focal neurologic dysfunction. The authors hypothesized that in patients with frontal–parietal–temporal brain tumors, focal neurologic deficits are unmasked or exacerbated by nonspecific sedation independent of the drug used. Methods This was a prospective, randomized, single-blind, self-controlled design with parallel arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 36 publications
3
39
0
1
Order By: Relevance
“…In our previous investigation, we found motor function and limb ataxia were the most affected. 6 In order to more accurately detect and quantify this deficit, the Nine-hole Peg Test has good reliability for testing upper limb dexterity, motor coordination, and hand-eye coordination, as well as patient ability to follow simple directions. 7,10 It therefore goes beyond assessing a single neurologic function confined to the tumor and its surroundings, but also assesses multiple functions reflecting the network connections between cortical and subcortical regions.…”
Section: Effect Of Glioma Grade On Task Performancementioning
confidence: 99%
See 2 more Smart Citations
“…In our previous investigation, we found motor function and limb ataxia were the most affected. 6 In order to more accurately detect and quantify this deficit, the Nine-hole Peg Test has good reliability for testing upper limb dexterity, motor coordination, and hand-eye coordination, as well as patient ability to follow simple directions. 7,10 It therefore goes beyond assessing a single neurologic function confined to the tumor and its surroundings, but also assesses multiple functions reflecting the network connections between cortical and subcortical regions.…”
Section: Effect Of Glioma Grade On Task Performancementioning
confidence: 99%
“…We speculated in our previous investigation that mild sedation-induced focal neurologic function worsening in patients with supratentorial intracranial lesions was likely transient and would return to baseline once the medications were no longer present on relevant receptors. 6 The sedative we used in this study is a specific benzodiazepine agonist: midazolam. It is a GABAergic agent that we previously found to most impair neurologic function, compared with other agents that have other pharmacologic mechanisms.…”
Section: Effect Of Glioma Grade On Task Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Patients with neurological diseases, e.g., brain tumors, are usually excluded in studies examining the correlation between anesthesia and neural function [8], as those diseases are major confounders leading to nervous system dysfunction, however, anesthetic effects on neural function cannot be ignored in neurosurgical patients, let alone the previously mentioned "vulnerable" brain tumor patient who is even more susceptible to anesthetics [9]. Recent findings have reported patients with supplementary motor area (SMA) lesions presenting with intraoperative neurological deficits for awake craniotomy which could not be explained anatomically by their intact corticospinal tracts as detected by cortical stimulation or cortical mapping [10,11], and these deficits were reversible after operations over time without further intervention.…”
Section: Subject Areasmentioning
confidence: 99%
“…It has been reported that in some supratentorial brain mass patients, a small plasma concentration of sedative could significantly worsen neurologic deficits before any operative intervention [9], but there is no evidence related to how residual anesthetics affect neurologic deficits after operations. are eligible for the study.…”
Section: Subject Areasmentioning
confidence: 99%